The Regulation of Strike Law in Times of New Technologies and Deregulation: The Case of West Germany - Mückenberger, Ulrich (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1990)
Although the West German law of strike has remained relatively unchanged in the last decade, various specifie legislative amendments, notably with respect to the payment of unemployment Insurance benefits during a labour conflict, to the domain of collective bargaining and to employee representation in the undertaking, could well alter the strike practice. The cumulative effect of these changes is examined in the perspective of a labour market evolving under technological change.